Uttarakhand Third Five-Year Plan Brief Progress Report 1964-65 (First Quarter April-June) - Government of Uttrakhand (Government of Uttarakhand, 1964)
The Uttarakhand Third Five-Year Plan Progress Report (1964–65) highlights significant developmental initiatives undertaken during the first quarter (April–June 1964) across multiple sectors. Key achievements include the expansion of horticulture farms, distribution of over 77,000 fruit plants, and substantial vegetable and fruit production. Minor irrigation and flood control projects were advanced with revised funding allocations, while forest and soil conservation efforts covered 62.5 acres and improved local communication. Animal husbandry services reached over 60,000 animals through hospitals and mobile clinics. Community development progressed with block-level initiatives, financial support for irrigation, and expansion of primary education to 416 schools. Investments in drinking water, sanitation, health infrastructure, mineral-based industries, and transport connectivity reflect a comprehensive approach to regional development. The report underscores financial commitments, community involvement, and the focus on enhancing quality of life in Uttarakhand through integrated planning and sustainable growth strategies.
Uttar Pradesh
Uttar Pradesh
Keywords: Uttarakhand; State Plan; Horticulture; Irrigation; Forestry; Animal Husbandry; Community Development; Education; Drinking Water; Public Health; Industry; Transport